Childhood hepatitis C virus infection: An Australian national surveillance study of incident cases over five years. (4th May 2015) - Raynes‐Greenow, Camille; Polis, Suzanne; Elliott, Elizabeth; Hardikar, Winita; Kesson, Alison; Kaldor, John; Jones, Cheryl A
Abstract : Aim: An estimated 1.1% of Australian adults are infected with hepatitis C virus (HCV). Many develop chronic liver disease, and some develop liver failure or hepatocellular carcinoma. HCV infection in Australian children is poorly defined. We aimed to determine the reported incidence, clinical and epidemiological features of newly diagnosed HCV infection in Australian children presenting to paediatricians. Methods: We undertook prospective active national surveillance, using the Australian Paediatric Surveillance Unit, of incident HCV cases in children aged <15 years between 1 st January 2003, and 31 st December 2007. Results: There were 45 confirmed cases of newly diagnosed HCV infection over five years (<1 per 100 000 children aged <15 years per year). Median age at diagnosis was 2.9 years. Positive maternal HCV serostatus was the most frequent reported risk factor for HCV infection in children (40/45). Three children (all aged > 14), were exposed through their own IV drug use. No children were co‐infected with HIV and only one child was co‐infected with HBV. All children were asymptomatic at diagnosis, although many had minor elevations in liver transaminases. Many clinicians reported difficulties with follow‐up. Conclusions: Childhood HCV infection is uncommon in Australia, although our data likely underestimate the incidence. Only a small number of children aged <18 months was identified, despite known perinatal exposure. Opportunistic investigation of children at risk for HCV, improved education regarding vertical transmission for health care providers, and increased coordination of childhood HCV services are required to improve recognition and management of children with HCV.